Understanding sustainability with Mark Lancelott (Assemble You, 2023)
In this episode of the Power Skills Project, Adam is joined by sustainability expert Mark Lancelott. Mark is an experienced sustainability consultant, keynote speaker, and thought leader who helps businesses respond to the opportunities and challenges of the sustainability crisis. He's led sustainability and circular economy projects across retail, consumer goods, manufacturing, and financial services for some of the biggest companies in the world, and for venture-backed start-ups and scale-ups. He's currently a Senior Client Partner at Korn Ferry and an adjunct faculty member at Hult Ashridge Executive Education. Adam and Mark go through what sustainability means, why it's so important as a business to be thinking about sustainability, and what as an individual you can do to encourage and support more sustainable behaviour.